If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 20x = 32 Solving X + 20x = 32 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-20x' to each side of the equation. X + 20x + -20x = 32 + -20x Combine like terms: 20x + -20x = 0 X + 0 = 32 + -20x X = 32 + -20x Simplifying X = 32 + -20x
| 2x-6x-23=0 | | 5(k+3)=25 | | 8y^2+9y-4=0 | | 6x-2x+6=36 | | 12x-5=7x+5 | | 3x+4=7x+8 | | y^4-y^2-72=0 | | 2p^2+5p=8 | | 7x-18=y+3 | | 11k+3=k+17 | | 7x-x=42 | | 7(y-3)=35 | | 2(3x-7)=2-10x | | -8=32-5x | | 2(4+x)=12 | | 9+7=29+5 | | 3x+12=2x-2 | | 6-7x=4(2x-6) | | 5y=10x+10 | | 6x+11=121-5x | | 8x^2-4x=24 | | 6x+2x=73.2 | | 8y=32 | | 3.5x+0.8=-16.7 | | 93+24k+26k=218 | | 3.5x+0.8=16.7 | | -2x-x+7x= | | 2.6=-0.4x | | 6x+2x=163.2 | | 7x-5x+5= | | 2p^2+6p=5 | | 28+12x=8x-4 |